ANALYSIS OF THE LITERATURE ON THE CONCEPTUAL FOUNDATIONS OF INFORMATION-PSYCHOLOGICAL SECURITY (Modern American Journal of Social Sciences and Humanities, 2025)
This article examines the experience of the People’s Republic of China among the leading foreign countries in the effective implementation of tasks related to ensuring the information-psychological security of the individual. This experience is aimed at the moral development of the individual and the formation of information culture and immunity against information-psychological threats.